'Flipping' the Lean Six Sigma classroom. (1st January 2014) - Kovach, Jamison V.; Carden, Lila L.; Ramos, Miguel A.
Lean and Six Sigma are well–known process improvement approaches; however, only a limited discussion about how to teach Lean Six Sigma in academia is available in the literature and these resources focus primarily on the use of traditional instructional delivery formats involving mainly face–to–face instruction. The purpose of this research is to describe an innovation for the Lean Six Sigma classroom - the incorporation of an interactive approach known as the 'flipped classroom', where passive, in–class lectures are replaced with more valuable activities traditionally completed by students outside of class such as having discussions or conducting hands–on learning exercises. Comparisons of student performance on certification exams and their perceptions about the course based on course evaluation scores indicates that this approach is at least as good as the traditional classroom approach; yet, it also provides working students with the flexibility and convenience needed to balance both their academic and professional priorities.